Building Prosperous, Healthy And Stunting-Free Families Empirical Study of Temanggung District - Widayanti, Ipuk Widayanti (Business Finence Analyst Co.,, 2024)
Stunting is a condition when a toddler has a minimum height or body length compared to their age. Factors that influence the occurrence of stunting in children under five in rural and urban areas are mother's education, family income, mother's knowledge of nutrition, exclusive breastfeeding, age at which MP-ASI is given, zinc and iron adequacy levels, history of infectious diseases and genetic factors. Activity objectives The output targets of this community service activity are increasing awareness of stunting prevention through improving parenting, understanding the role of housewives, increasing knowledge about financial literacy in the family, and understanding the nutritional needs of pregnant women. Community service activities were carried out in the Tingkir Tengah Village meeting room with the target of involving 45 representatives from 10 RW. Participants consisted of Posyandu cadres, PKK cadres, dashat cadres, and Pregnant Women. Community service activities went well according to plan. The event was attended by more than 80% of invited participants consisting of posyandu cadres, dashat cadres, and pregnant women. This activity is expected to increase knowledge so that reduction and prevention of stunting can be implemented